Magnolol induces cell death through PI3K/Akt‐mediated epigenetic modifications boosting treatment of BRAF‐ and NRAS‐mutant melanoma. (21st February 2019) - Emran, Abdullah Al; Chinna Chowdary, Brinda Reddy; Ahmed, Farzana; Hammerlindl, Heinz; Huefner, Antje; Haass, Nikolas K.; Schuehly, Wolfgang; Schaider, Helmut
Abstract: Most BRAF ‐mutant melanoma patients experience a fulminate relapse after several months of treatment with BRAF/MEK inhibitors. To improve therapeutic efficacy, natural plant‐derived compounds might be considered as potent additives. Here, we show that magnolol, a constituent of Magnolia officinalis, induced G1 arrest, apoptosis and cell death in BRAF‐ and NRAS‐ mutant melanoma cells at low concentration, with no effect in BRAF‐ and NRAS wild‐type melanoma cells and human keratinocytes. This was confirmed in a 3D spheroid model. The apoptosis‐inducing effect of magnolol was completely rescued by activating Akt suggesting a mechanism relying primarily on Akt signaling. Magnolol significantly downregulated the PI3K/Akt pathway which led to a global decrease of the active histone mark H3K4me3. Alongside, the repressive histone mark H3K9me3 was increased as a response to DNA damage. Magnolol‐induced alterations of histone modifications are reversible upon activation of the Akt pathway. Magnolol‐induced a synergistic effect in combination with either BRAF/MEK inhibitors dabrafenib/trametinib or docetaxel at a lower concentration than usually applied in melanoma patients. Combination of magnolol with targeted therapy or chemotherapy also led to analogous effects on histone marks, which was rescued by Akt pathway activation. Our study revealed a novel epigenetic mechanism of magnolol‐induced cell death in melanoma. Magnolol might therefore be a clinically useful addition to BRAF/MEK inhibitors with enhanced efficacy delaying or preventing disease recurrence. Abstract : To improve treatment of BRAF/MEK inhibitors and chemotherapy in BRAF/NRAS mt melanoma, the benefit of the plant‐derived compound magnolol alone or in combination has been investigated. Magnolol decimated BRAF/NRAS mt cancer cells alone or in combination albeit at a lower dosage than magnolol alone. Mechanistically, magnolol‐induced cell death in BRAF/NRAS mt melanoma through PI3K/Akt dependent epigenetic remodeling.